IN MEMORY OF ZARAB GAZIZOVICH KAZIEV - Sarpekov, Рамазан Кумарбекович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2021)
The article is devoted to the life, professional and practical and scientific activities of the colonel of the national security bodies of the Republic of Kazakhstan, Honorary pensioner of the national security bodies, head of the department of criminal, criminal procedure and criminal executive legislation of the Institute of Legislation and Legal Information of the Republic of Kazakhstan, Candidate of Legal Sciences, Professor Kaziev Zarab Gazizovich. The article describes the early life of Z.G. Kaziev, the period of his professional activity in the national security agencies, the Academy of the National Security Committee, the Institute of Legislation and Legal Information of the Republic of Kazakhstan. The article shows the path of Zarab Gazizovich's formation as a scientist: defense of a Ph.D. thesis, participation in the training of highly qualified scientific and pedagogical personnel, opposition on dissertations for the degree of candidate of legal sciences, obtaining the academic title of "professor", researching legal monitoring issues, conducting fundamental and applied scientific research in the field of criminal procedural law, operational-search activity. The role of Z.G. Kaziev in the legal reforms carried out by the state - the development of the Decree of the President of the Republic of Kazakhstan «On the National Security Bodies» in 1995, the drafts of the Criminal Procedure Code of December 13, 1997, the Law «On Forensic Expertise» of November 12, 1997. An important milestone in the life of Zarab Gazizovich was the study of archival materials on persons accused of counter-revolutionary and other hostile activities during the years of mass repressions against unrehabilitated victims of forcibly deported peoples and special settlers the highly competent role of Z.G. Kaziev in an expert assessment of the implementation of a three-tier model with the delineation of powers and areas of responsibility between law enforcement agencies, the prosecutor's office and the court. During his career, Zarab Gazizovich was awarded medals and various departmental awards, had numerous awards, was an honorary pensioner of the national security agencies, the author of over 100 scientific, scientific and methodological and educational and methodological works.